A Novel Serum tsRNA for Diagnosis and Prediction of Nephritis in SLE - Yang, Ping; Zhang, Xiaoshan; Chen, Shanshan; Tao, Yue; Ning, Mingzhe; Zhu, Yijia; Liang, Jun; Kong, Wei; Shi, Bo; Li, Zhiyang; Shen, Han; Wang, Yanbo (Frontiers in Immunology, 2021)
Object: Dysregulation of tRNA-derived small noncoding RNA (tsRNA) signatures in human serum has been found in various diseases. Here we determine whether the signatures of tsRNAs in serum can serve as biomarkers for diagnosis or prognosis of systemic lupus erythematosus (SLE). Methods: Initially, small RNA sequencing was employed for the screening serum tsRNAs obtained from SLE patients, followed by validation with TaqMan probe-based quantitative reverse transcription-PCR (RT-PCR) assay. Receiver Operating Characteristic Curve (ROC) analysis was used to assess the diagnostic efficacy. The biological functions of tsRNAs were identified by GO and KEGG assay. Results: We first analyzed tsRNA signatures in SLE serum and identified that tRF-His-GTG-1 was significantly upregulated in SLE serum. The combination of tRF-His-GTG-1 and anti-dsDNA could serve as biomarkers for diagnosing SLE with a high AUC of 0.95 (95% CI=0.92-0.99), sensitivity (83.72%) and specificity (94.19%). Importantly, the non-invasive serum tRF-His-GTG-1 could also be used to distinguish SLE with LN or SLE without LN with AUC of 0.81 (95% CI, 0.73–0.88) and performance (sensitivity 66.27%, specificity 96.15%). Moreover, the serum tsRNA is mainly secreted via exosome and directly target signaling molecules that play crucial roles in regulating the immune system. Conclusion: In this study, it has been demonstrated for the first time that serum tsRNAs can be employed as non-invasive biomarkers for the efficient diagnosis and prediction of nephritis in SLE.